Analysis, Design and Optimization of Electric Vehicle Wireless Chargers - González-González, José Manuel (UMA Editorial, 2021)
Nowadays, one of the biggest concerns of potential users of these vehicles is their autonomy, which is limited both by the capacity of the batteries and by their charging. Wireless charging, especially magnetic-resonance technology, is considered a real alternative to conductive charging as it provides additional advantages such as greater security and ease of charging. This technology has a very rich field of development to which this thesis has contributed in a number of aspects. The first of these contributions lies in the analytical characterization of the magnetic field generated by inductive chargers. This tool, which has been validated with a 3.7-kW wireless charger prototype, facilitates the design tasks of coils, as well as the control of the exposure of external objects to the magnetic field. One of the main difficulties that wireless chargers will have to face lies in the future transition to this technology. Wireless technology is expected to coexist with conductive technology. This thesis provides an on-board hybrid solution to facilitate the transition. Developing prototypes is essential for implementing and analysing new solutions. In addition to a prototype for development purposes, we have designed and implemented a final prototype for charging an electric bicycle. The charging strategy is not the only relevant aspect that controllers must monitor. The operation of the chargers outside their nominal conditions, such as in the case of misalignment between coils, produces an increase in some electrical variables of the circuit that must be controlled. The control of wireless chargers also affects efficiency, which will play a fundamental role in the adoption of this technology as it is the main disadvantage compared to conductive chargers. The final contribution of this Thesis focuses on this aspect, for which a Model Predictive Control (MPC) is proposed.
Keywords: Vehículo eléctrico; Carga inalámbrica; Transferencia de potencia por resonancia magnética; Modelo de control predictivo; Máxima eficiencia